Investigating the Frequency Spectrum Characteristic of Stress Wave under Multistage Loading Stress - Yun Cheng; Zhanping Song; Xiaoxu Chang; Tengtian Yang (Advances in Civil Engineering)
The stability of rock mass is destroyed by natural or human activities and leads to stress redistribution, causing the rock mass in a certain stressful environment. This study conducted a small disturbance impact tests on sandstone bar under loading stress by modified split Hopkinson pressure bar (SHPB). The results show that the reflection and transmission characteristics of stress wave are affected due to the loading stress changes in the sandstone porosity. The loading stress has a specific effect on the frequency spectrum distribution of the stress wave. The frequency spectrum curve has gone through the three stages, a gradual increase, then rapid attenuation, and finally a smooth development with the frequency increasing, and its dominant frequencies are mainly concentrated in 0∼2 kHz. The loading stress has a significant influence on the variation tendency of the dominant frequency. The dominant frequency experiences a slow increase and then tends to be stable, and the total energy of the frequency band shows a fast attenuation and then a gentle development, and its stress boundary point is σ/σc = 30%. The total energy attenuates as a first-order exponential function and its attenuation rate shows an exponential-linear function with the increasing loading stress, the farther away from the shock end, the faster the total energy attenuation is. The sandstone can filter the high-frequency wave and the low-frequency wave can penetrate rock media better. The closer the distance to the impact source, the greater the total energy of the frequency band. The frequency band energy is mainly concentrated in 0∼36.62 kHz, the higher the frequency of the frequency band is, the smaller the energy ratio is. Therefore, those conclusions can provide a reference for the evolution analysis of the stress wave spectrum in an excavated rock mass.